2021
DOI: 10.1007/s40744-021-00360-6
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Inflammatory Bowel Disease Adverse Events with Anti-Interleukin 17A Agents and Tumor Necrosis Factor Inhibitors in Rheumatic Disease and Skin Psoriasis

Abstract: Introduction: The aim of this work is to perform a systematic review and meta-analysis of anti-tumor necrosis factor (anti-TNF) and antiinterleukin-17 (anti-IL-17) trials for spondyloarthritis, psoriatic arthritis, and psoriasis comparing rates of inflammatory bowel disease (IBD) events compared to placebo.Methods: MEDLINE, EMBASE, and The Cochrane Library were searched for doubleblind, randomized placebo-controlled anti-TNF and anti-IL-17 trials of included diseases. Inflammatory bowel disease events from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Side effects of IL-17 inhibitors include injection site reactions, increased risk of infection, nasopharyngitis, candida infections, diarrhea, neutropenia, and nausea. IL-17 inhibition has been reported to contribute to the development or unmasking of inflammatory bowel disease, but a recent systematic review did not find a link [ 98 ]. The paradoxical development of HS has also been reported after treatment with secukinumab [ 34 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Side effects of IL-17 inhibitors include injection site reactions, increased risk of infection, nasopharyngitis, candida infections, diarrhea, neutropenia, and nausea. IL-17 inhibition has been reported to contribute to the development or unmasking of inflammatory bowel disease, but a recent systematic review did not find a link [ 98 ]. The paradoxical development of HS has also been reported after treatment with secukinumab [ 34 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…17 This incidence is comparable to that seen with other IL-17 inhibitors. [50][51][52] Specifically, a meta-analysis found the EAIR of IBD for both secukinumab and ixekizumab to be 0.23 per 100 personyears and pooled data from five clinical trials for brodalumab found its EAIR of IBD to be 0.2 per 100 person-years. 51,52 Although these rates are low, the panel recommends considering other biologic therapies for psoriasis first in patients with IBD.…”
mentioning
confidence: 99%
“…[50][51][52] Specifically, a meta-analysis found the EAIR of IBD for both secukinumab and ixekizumab to be 0.23 per 100 personyears and pooled data from five clinical trials for brodalumab found its EAIR of IBD to be 0.2 per 100 person-years. 51,52 Although these rates are low, the panel recommends considering other biologic therapies for psoriasis first in patients with IBD. Methotrexate, cyclosporine, and acitretin were some of the first systemic therapies used in the treatment of plaque psoriasis and are commonly used to this day.…”
mentioning
confidence: 99%